Cooperative Loan Eligibility Determination System Using The Evaluation Based on Distance form Average Solution (EDAS) Method - Aina Rahmadani; Wahyu Fuadi; Ar Razi (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
The rapid development of Decision Support Systems (DSS) has provided significant benefits, especially in supporting decision-making across various fields, including determining credit loan eligibility within cooperatives. Loans involve transactions in which lenders provide funds or assets to borrowers under agreed-upon terms. DSS is essential for enhancing objectivity and reducing the risk of non-performing loans arising from subjective evaluations. This study produces a web-based DSS capable of evaluating the loan eligibility of cooperative members by implementing the Evaluation Based on Distance from Average Solution (EDAS) method, combined with Rank Order Centroid (ROC) weighting. The system analyzes several criteria, such as collateral, membership status, loan amount, loan term, income, remaining loan balance, and payment status. The EDAS method generates a ranking based on eligibility, with alternative N0071 achieving the highest score of 0.907, followed by N0004 with a score of 0.830, and N0019 with a score of 0.762. The results of the system testing indicate that the loan eligibility calculations produced by the system are accurate and consistent with manual calculations, achieving a match of 95%. This ranking simplifies the cooperative's decision-making process. Furthermore, the system accelerates the loan eligibility determination process, enabling cooperatives to serve their members more effectively and efficiently.